"Dose dense" chemotherapy in ovarian cancer. (1st November 2005) - VASEY, P. A.
Abstract : In essence, dose densification is "accelerated therapy" (a commonly used phrase in radiotherapeutics) and is a form of dose intensification because the amount of drug per unit time (dose intensity = mg/m 2 /week) is increased. There is general consensus that increasing platinum dose intensity in ovarian carcinoma has not been proven despite a dozen or more randomized trials evaluating up to twofold increases in dose intensity. Few randomized trials in ovarian carcinoma have compared weekly "dose dense" chemotherapy with more conventional dosing schedules although there are plenty of phase II studies. In these, dose densification of single agent therapy, for some drugs at least, appears to be relatively well tolerated, with encouraging levels of activity in patients purportedly refractory to the same agents when scheduled in the standard way. However, many studies ostensibly evaluating "dose density" do not actually evaluate this entity, but actually split the standard 3-weekly dose into weekly fragments thus maintaining the same dose intensity. Furthermore, as the aim of treatment in recurrent ovarian cancer is palliation, weekly treatments are less convenient, are probably less cost effective, and have different dose-limiting toxicities. This article will review the clinical data supporting dose density as a therapeutic maneuver in ovarian cancer.